2015
DOI: 10.1002/chem.201502076
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Tyrosine into Controlled Supramolecular Nanostructures

Abstract: In the context of designing novel amino acid nanostructures, the capacity of tyrosine alone to form well-ordered structures under different conditions was explored. It was observed that Tyr can self-assemble into well-defined morphologies when deposited onto surfaces for transmission electron microscopy, atomic force microscopy, and scanning electron microscopy. The influence of various parameters that can modulate the self-assembly process, including concentration of the amino acid, aging time, and solvent, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 55 publications
4
73
0
Order By: Relevance
“…demonstrated that aqueous solutions of free unprotected phenylalanine form amyloid-like fibrillary structures that may contribute to the etiology of phenylketonuria 14 . Tyrosine and tryptophan have also been shown to assemble into nano- and microscale architectures 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that aqueous solutions of free unprotected phenylalanine form amyloid-like fibrillary structures that may contribute to the etiology of phenylketonuria 14 . Tyrosine and tryptophan have also been shown to assemble into nano- and microscale architectures 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a number of peptidebased building blocks related to these amino acids have been designed and developed to create supramolecular structures (Zhou et al, 2017;Lee et al, 2018). Moreover, the amino acids Phe and Tyr have been shown to be capable of self-assembling into supramolecular nanostructures (Adler-Abramovich et al, 2012;Singh et al, 2014;Mé nard-Moyon et al, 2015). Even though it is feasible for both Tyr and Phe-based fragments to be part of self-assembly processes, the structural difference associated with the phenolic OH group, as a side-chain functional group in Tyr, seems to be critical for the structural features and properties of the resultant entity.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the aromatic l -Tyrosine (Tyr) amino acid was found to form amyloid-like fibrils [ 13 , 18 ]. The accumulation of Tyr occurs in three different types of tyrosinemia, all resulting from autosomal recessive mutations in several genes in the phenylalanine (Phe) and Tyr metabolic pathway [ 19 ].…”
Section: Introductionmentioning
confidence: 99%